Methods of developing the coordination skills of preschool children through non-traditional exercises - Hamitova Maftuna Sayfiddin qizi (Genius Journals, 2022)
This article discusses ways to develop the coordination skills of preschool children through non-traditional exercises. It explains what to pay attention to in the development of coordination skills and the stages of development of coordination skills in accordance with age characteristics.
Keywords: Coordination skills; agility; physical qualities; gymnastics